(untitled) (American Journal of Islam and Society, 2018)
At the turn of the nineteenth century, a movement of religious reform and state building took place in present-day northern Nigeria, culminating with the establishment of the Sokoto Caliphate. This movement was as central to West African history as was the 1789 French revolution to European history. Its leader, the Muslim scholar Uthman Dan Fodio (d. 1817), deserves recognition as a towering figure of nineteenth-century African Islam. Dan Fodio’s community (jamā‘a), which included many scholars, toppled the preexisting Hausa kingdoms, replacing them with emirates ruled by Fulani leaders who all paid allegiance to the Caliph based in Sokoto. At its zenith, the Caliphate, which became the most powerful economic and political entity of West Africa in the nineteenth century, linked over thirty different emirates and over ten million people ...